2022
DOI: 10.3390/molecules27144360
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Melanogenesis in B16 Cells Upon Treatment with Plant Extracts and Isolated Plant Compounds

Abstract: Plants are a rich source of secondary metabolites that exhibit numerous desired properties. The compounds may influence the biology of melanocytes, pigment cells that produce melanin, by modulating numerous signaling pathways, including cAMP/PKA, MAPKs and PI3K/AKT. Its downstream target is microphthalmia-associated transcription factor, responsible for the expression of the tyrosinase enzyme, which plays a major role in melanogenesis. Therefore, this literature review aims to provide insights related to melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 166 publications
0
14
0
Order By: Relevance
“…Therefore, we evaluated the influence of imperatorin on melanogenesis-related enzymes to understand the melanogenesis stimulation mechanisms of imperatorin in detail. Melanogenesis is directly regulated by the major enzymes TRY, TYRP-1, and TYRP-2 [ 44 , 45 ]. In this study, imperatorin significantly increased the expression of TRY, TYRP-1, and TYRP-2, which is consistent with the results observed for melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we evaluated the influence of imperatorin on melanogenesis-related enzymes to understand the melanogenesis stimulation mechanisms of imperatorin in detail. Melanogenesis is directly regulated by the major enzymes TRY, TYRP-1, and TYRP-2 [ 44 , 45 ]. In this study, imperatorin significantly increased the expression of TRY, TYRP-1, and TYRP-2, which is consistent with the results observed for melanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, inhibition of MITF activity leads to reduced melanin production, while in some others, stimulation of MITF activity results in increased melanin production. Both the effects may be achieved through implementation of plant-derived compounds [ 60 ]. Therefore, these molecules may exert a beneficial therapeutic effect on skin of patients with hyperpigmentation or hypopigmentation, including postinflammatory hyperpigmentation, solar lentigines, melasma, café au lait macules, ephelides (freckles) as well as postinflammatory hypopigmentation, vitiligo, pityriasis alba, tinea versicolor [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Plant Extract and Pure Compounds–biological Properties And M...mentioning
confidence: 99%
“…Detailed analyses of the modulation of melanogenesis upon treatment with plant extracts and isolated plant compounds in in vitro model were presented in our previous study [ 60 ]. However, selected investigations of plant extracts and pure plant compounds on in vivo models, given above, were also conducted on melanocyte monocultures.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Other studies also revealed that -keto group in mangosteen peel have a structure such as dihydroxyphenylalanine (DOPA) or tyrosine that could prevent melanogenesis in skin-induced UVB radiation [15], [16]. Physical and chemical characterization of mangosteen peel has been already reported by previous studies [11], [12], [13], [14], [15], [16]; however, the potency of the mangosteen peel extract-based cream and its mechanism in skin hyperpigmentation is still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…The previous studies reported that the mangosteen peel contains phenolic and flavonoid polyphenols, both of which include phenol rings with one or more hydroxyl substituents that may scavenge ROS as a result of exposure to UVB radiation [13], [14]. Other studies also revealed that -keto group in mangosteen peel have a structure such as dihydroxyphenylalanine (DOPA) or tyrosine that could prevent melanogenesis in skin-induced UVB radiation [15], [16]. Physical and chemical characterization of mangosteen peel has been already reported by previous studies [11], [12], [13], [14], [15], [16]; however, the potency of the mangosteen peel extract-based cream and its mechanism in skin hyperpigmentation is still unknown.…”
Section: Introductionmentioning
confidence: 99%